Modern African drama : backgrounds and criticism 2026-02-16T00:55:22+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Jeyifo, Biodun, 1946- (A Norton critical edition, 2002)

(untitled)
Presents eight twentieth-century plays from seven African countries, along with explanatory notes and over thirty background writings and works of criticism